(3eTGQb GdCfhGQ GdfHhjI ef UMGM GdCNHGQ GdeUWahjIs - (3GdQVj GdUGZGfj , GdMSf Hf eMeO Hf GdMSf Hf MjOQ, QVj GdOjf,J (B650 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eMi GdQeje , heLQi Gdbde CeG HYO aEfi efP JOQLJ eQGKi GdTQa hJNQLJ ef eSGbi GdTQa s
(3BNQgG (B:s
(3dHjc YeQI hMLkG Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG ebGHdGJ hHChdgG agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B279s
Keywords: (3GdMOjK h GdeUWdMs